(Post)Dramatic Strategies: Performing Difference in Pat Kinevane's Solo Theatre. Issue 2 (November 2021) - Mallon, Clara
Abstract : Pat Kinevane's solo performances focus on identities constituted on the margins of contemporary Irish society. Fusing the comic with the tragic, improvisation with carefully planned execution, and entertainment with serious cultural critique, these performative works range freely through diverse theatrical styles to represent Irish characters marginalized by their communities. Utilizing Hans-Thies Lehmann's ideas in Postdramatic Theatre (2006), this essay demonstrates how Kinevane's theatre inscribes but also contests some of the modalities of postdramatic discourse, creating a platform through which hegemonic political frameworks are challenged and identities are presented outside the established social norm. Through a performative analysis of the constructional, formal, and stylistic techniques, I argue that Kinevane's combined use of dramatic and postdramatic strategies can be seen as an essential part of his attempts to create consciousness raising and promote critical thinking among audiences.